Hypomelanosis of Ito: Neurocuteneous Syndrome - Ghosh, Uzzal Kumar; Kaes, Md Imrul; Al Mamun, Md Abdul Hadi; Razzaque, Md Abdur (KYAMC Journal, 2022)
A 7-year-old girl, 2nd issue of non-consanguineous parents hailing from Rajshahi got attended to our outpatient department of Pediatrics with the complaints of white patches all over the body since early infancy, poor intelligence, and speech problems. There was history of developmental delay but no history of seizures or visual problems or hearing impairment. She also had dental abnormalities. Family history was not significant. For these she treated with several oral and local antibacterial, antifungal and corticostresoid medications, but no improvement. Examination revealed symmetrical hypopigmented patches involving the trunk and upper limbs, and were following Blaschko’s lines. Anthropometry and others examination were normal. The hearing assessment was normal. There were no ocular abnormalities but have delayed dentation with mal-alignment of teeth with carries. She have moderate level of intellectual disability (ID). Our diagnosis was hypomelanosis of Ito (HI); a rare type of neurocuteneous syndrome. Routine investigations were normal, CT scan of the brain showed mild cortical atrophy, EEG was normal. The parents were counseled about the recent level of intellectual functioning, asked to allow the child for learning self-help skills, and referred to a child development center, child psychologist, and speech therapist. Our patients were well and no complications were observed till writing this report. We like to share our experience of diagnosing and treating this very rare disease of HI. KYAMC Journal Vol. 13, No. 02, July 2022: 120-123